P1-S2.25 HIV serostatus knowledge, absence of previous testing and sexual behaviours among injecting drug users. (10th July 2011) - Blouin, K; Parent, R; Leclerc, P; Blanchette, C; Alary, M; Morissette, C; Roy, É; Claessens, C
Abstract : Background: Few studies have examined the association between HIV status knowledge and sexual behaviours among injection drug users (IDUs). We tested the hypothesis that IDUs who know their HIV positive status will have safer sexual practices than IDUs aware of their HIV negative status or never tested for HIV. Methods: IDUs who had injected in the past 6 months were recruited in harm reduction programs across the Province of Quebec and Ottawa, Canada. Participants completed a questionnaire including questions on sexual behaviours and provided saliva for HIV antibody testing. For IDUs with multiple participations, the last interview was selected. Data from 2003 to 2009 were analysed. Three groups were compared—IDUs aware of their positive HIV status (n=510), IDUs aware of their HIV negative status (n=2928) and IDUs never tested for HIV (n=427). Proportions were compared using χ 2 tests. Results: Male IDUs aware of their positive HIV status were less likely to have had sex in the last month (HIV positive—32.4%, HIV negative—47.2% and never tested—55.0%; p<0.0001, n=2741) and, among those sexually active, more likely to have used a condom at last sexual intercourse (HIV positive—57.4%, HIV negative—43.7% and never tested—51.7%; p<0.005, n=1249). This was not observed for women. In the last 6 months, the proportion of male IDUs who had always used condoms for vaginal or anal sex with their female sex partners was significantly higher in HIV positive than in HIV negative and in those never tested, for regular (54.3%, 22.4% and 33.1%, respectively, p<0.0001, n=1131), casual (77.4%, 54.4% and 51.2%, respectively, p=0.0002, n=933) and partners of whom they are a client (86.7%, 69.7% and 42.1%, respectively, p<0.02, n=123). Women never tested for HIV were less likely than the other groups to use condoms with their regular partners (never tested—4.7%, HIV positive—21.3% and HIV negative—20.2%; p<0.05, n=550) and their client sex partners (never tested—46.2%, HIV positive—82.1% and HIV negative—76.6%; p<0.05, n=259). Women aware of their HIV positive status were more likely to report condom use with their casual sex partners, whereas those never tested were less likely (HIV positive—66.7%, HIV negative—48.0% and never tested—15.8%; p<0.01, n=250). Conclusions: IDUs aware of their positive HIV serostatus reported more consistent condom use with their various types of sex partners than those aware of their HIV negative status or never tested.